Global Existence of Solutions for a System Modelling Electromigration of Ions Through Biological Cell Membranes with L1 Data (European Journal of Pure and Applied Mathematics, 2017)
The aim of this work is to show the existence of weak solutions and supersolutions for a nonlinear system modelling Ions migration through biological cells membranes with L1- Data. In the first step, we describe the mathematical model after that we define an approximating scheme.Under simplifying assumptions on the model equation, we prove some L1 a priori estimates, then we prove that the solution of the truncated system converges to the solution of our main problem.
Keywords: Reaction diffusion; globale existence; L1 data; Truncated function; supersolution and subsolution